Can one-wall bone defects be augmented with xenogenic bone grafting material alone?. Issue 9 (September 2016) - Mehl, Christian; Kern, Matthias; Meinke, Niclas; Açil, Yahya; Bähr, Telse; Wiltfang, Jörg; Gaßling, Volker
Abstract: Objectives: The main aim of this study was to evaluate the impact of xenogenic bovine bone grafting material particle size, addition of harvested autogenic bone as well as the influence of a periosteum on growth of newly formed bone, bone marrow, residual bone grafting material and connective tissue of one-wall defects. Methods: Overall 32 augmentation sites were placed on the frontal skull of four minipigs and covered with titanium pin immobilized absorbable porcine membranes. After a 6 month healing period the harvested specimens were analyzed using light- and fluorescence microscopy. Results: In the augmented areas 47%–57% bone, 14%–34% bone marrow, 10%–20% residual xenogenic bone grafting material and 4.5%–10% connective tissue were found. Admixture of autogenic bone resulted in statistically significantly more newly formed bone, more bone marrow, less residual xenogenic bone grafting material and less connective tissue (P ≤ 0.03). Conclusions: While augmenting one-wall defects seems to be possible with xenogenic grafting material and absorbable membranes alone, the addition of autogenic bone seems to benefit the augmentation site.